Penafsiran, Ideologi, dan Afiliasi Politik: Kritik Buya Hamka (1908-1981 M) terhadap Nasakom Era Demokrasi Terpimpin (1959-1966 M) - Fitra, Akhmad Aidil; Wendry, Novizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Criticism of socio-political phenomena through the interpretation of the Qur'an as a medium to legitimise the claims of criticism expressed, is often used by mufassirs. As Buya Hamka did, he used his interpretation to criticise the Nasakom political ideology in the era of Guided Democracy under the leadership of Soekarno. Therefore, the purpose of this research is to find out how Buya Hamka criticised Nasakom in Al-Azhar. Using descriptive, historical and explanatory methods. The research findings are as follows. First, Buya Hamka was a cleric who was critical of the policies of the Guided Democracy regime. Especially if the policy was considered contrary to Islamic law, such as Nasakom syncretism. Although the regime was repressive, Buya Hamka remained steadfast in fighting for the interests of Islamic ideology. Secondly, Buya Hamka made Al-Azhar as a medium to respond and criticise the socio-political reality that developed at that time. Interestingly, the criticism expressed did not come out of the main meaning of the Qur'anic text. Third, Buya Hamka's criticisms were able to disrupt the political escalation of the government, at least giving vibrations to the body of power, even though the Soekarno regime tried to muffle but he was able to get out of the massive pressure. Starting from the banning of Panji Masyarakat magazine until the climax he was imprisoned.